Za głosem Penelopy - Bibik, Barbara (Collectanea Philologica, 2016)
Following the voice of Penelope is the review of a play based on one of the Homer’s greatest epic poem – Odyssey, staged by Ondrej Spišák in the Warsaw puppet theatre „Teatr Lalka”. This artistically beautiful, full of magic and awarded staging, first performed in 1999, still finds its audience. It is definitely worth spending an hour in the theatre to see this enchanting ancient world created on the Warsaw stage and directed by Homer himself.